Positive body image, intuitive eating, and psychosocial functioning among older women: Testing an integrated model. (April 2022) - Rodgers, Rachel F.; Berry, Rachel; Laveway, Katherine; Carrard, Isabelle
Abstract: Background: Research on the body image and eating behaviors of older women is scarce. Moreover, the scant existing research has lacked a focus on positive dimensions, such as positive reappraisal and acceptance, body appreciation, appearance satisfaction, and intuitive eating among older women. Therefore, the aim of the present study was to examine a model of the relationships among these positive dimensions and psychological functioning in older women. Methods: A sample of 171 women aged 60–75 years were recruited through social media to respond to a survey assessing body image, eating behaviors, and psychological wellbeing. Results: The final model was a good fit to the data. In this model, positive reappraisal and acceptance of age-related appearance changes was associated with higher body appreciation, in turn associated with higher body image related quality of life, higher levels of intuitive eating, and lower levels of depressive symptoms. Conclusion: Positive body image and positive reappraisal of aging-related changes in appearance are associated with psychological wellbeing among older women. Longitudinal data are needed to clarify the direction of these relationships and inform interventions. Body image remains an important dimension among older women and should be accounted for in broader health promotion efforts among this group. Highlights: Positive body image and intuitive eating were assessed among older women. Positive reappraisal and acceptance of aging was associated with both outcomes. Positive reappraisal correlated with appearance satisfaction and body appreciation. These variables were associated with intuitive eating and psychological wellbeing.